Pengaruh Financial Leverage dan Operating Leverage Terhadap Profitabilitas pada Perusahaan Sektor Transportasi yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022 - Rizky Utami, Adinda; Suprihatmi SW; Indriastuti, D. Ririn (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Profitability is the company's ability to generate profits using the resources within the company itself in a certain period. The higher this ratio, the better it means that the position of the company owner is getting stronger. The purpose of this study was to analyse the significance of the effect of financial leverage and operating leverage on profitability. The population in this study are transportation sector companies listed on the Indonesia Stock Exchange in 2020-2022. The sampling technique of this study used purposive sampling method, so that a sample of 28 companies was obtained. The data analysis technique in this study used multiple linear regression analysis, t test, F test, and coefficient of determination (????2). This study partially shows that financial leverage has a significant positive effect on profitability in transportation companies listed on the Indonesia Stock Exchange during the period 2020-2022. Operational leverage was also found to have a significant positive effect on profitability in transportation companies listed on the Indonesia Stock Exchange during the same period. Simultaneously, financial leverage and operational leverage have a significant effect on the profitability of these transportation companies. The results of the analysis of the coefficient of determination (adjusted R2) of 0.175 indicate that the independent variables X1 (financial leverage) and X2 (operational leverage) explain 17.5% of the variation in profitability (Y). The remaining 82.5% (100% - 17.5%) is explained by other variables outside the model, such as working capital turnover, liquidity, firm size, debt-to-equity ratio (DER), and capital structure.